Cuidados de enfermería en pacientes adultos oncológicos en quimioterapia para prevención de efectos adversos - Lema Pilco, Lucila Ximena (2025)
Cancer is one of the main health concerns worldwide due to its high incidence and mortality. Chemotherapy is the most common treatment, but it can generate adverse effects that affect the patient's physical, emotional and social health. Nursing care is essential to mitigate these effects and improve the patient's quality of life. Despite advances in oncology, chemotherapy administration remains complex and can cause side effects such as alopecia, skin toxicity and myelosuppression. The aim of this research is to identify nursing care in adult cancer patients undergoing chemotherapy focused on reducing adverse effects. For this purpose, a systematic review was carried out and it is a descriptive and narrative cross-sectional study, with a qualitative approach using the PRISMA method. The systematic search was carried out using the PICO structured question based strategy. Twenty selected scientific articles on nursing practices for the management of adverse effects of chemotherapy were included. The results that stand out are constant monitoring, self-care education, symptom management and emotional support that are essential to improve the patient's experience and quality of life, the importance of a collaborative approach among professionals and the use of innovations such as telemedicine to reduce complications and improve follow-up were highlighted. Nurses have a crucial role in the comprehensive care of the oncology patient, helping to prevent and manage these effects.